What are the sustainable palm oil initiatives that guide and support smallholders in Indonesia? - Chua, Li-Ann (Nanyang Technological University, 2025)
This project investigates the nature of sustainable palm oil initiatives in Indonesia, with a focus on how they support smallholders—both independent and scheme-based—in becoming more sustainable, and additionally in achieving Roundtable on Sustainable Palm Oil (RSPO) certification. Through a systematic online literature review, 32 initiatives were identified and analysed across two dimensions: (1) thematic and strategic composition, including environmental versus socio-economic focus and types of upgrading activities; and (2) alignment with RSPO certification requirements, using the 2024 RSPO and RSPO Independent Smallholder (ISH) standards as benchmarks. Results reveal a strong emphasis on environmental outcomes, with an average of 63.7% of initiative features being environmentally focused. Upgrading activities were also skewed, with process and functional upgrading dominating, while product and inter-sectoral upgrading—key for long-term resilience—were notably limited. Certification alignment analysis found that most non-certification-linked initiatives demonstrated low scores, with most support clustering around Good Agricultural Practices (GAPs). Features related to financing, market incentives, and systemic enablers were largely absent from formal RSPO criteria, despite being essential to smallholder inclusion. These findings highlight a narrow implementation strategy that prioritises technical and operational interventions, while under-addressing socio-economic and structural constraints. Without greater attention to enabling conditions like financial access, premium guarantees, and inclusive upgrading pathways, many smallholders, particularly the most vulnerable, risk continued exclusion from sustainable palm oil systems. The methodology developed in this study provides a scalable framework for assessing initiative design and tracking progress toward inclusive certification outcomes over time.